Evaluation of the Hippocampal Normal Tissue Complication Model in a Prospective Cohort of Low Grade Glioma Patients—An Analysis Within the EORTC 22033 Clinical Trial - Jaspers, Jaap; Mèndez Romero, Alejandra; Hoogeman, Mischa S.; van den Bent, Martin; Wiggenraad, Ruud G. J.; Taphoorn, Martin J. B.; Eekers, Danielle B. P.; Lagerwaard, Frank J.; Lucas Calduch, Anna Maria; Baumert, Brigitta G.; Klein, Martin (Frontiers in Oncology, 2019)
Purpose: To evaluate the performance of the hippocampal normal tissue complication model that relates dose to the bilateral hippocampus to memory impairment at 18 months post- treatment in a population of low-grade glioma (LGG) patients. Methods: LGG patients treated within the radiotherapy-only arm of the EORTC 22033-26033 trial were analyzed. Hippocampal dose parameters were calculated from the original radiotherapy plans. Difference in Rey Verbal Auditory Learning test delayed recall (AVLT-DR) performance pre-and 18 (+/- 4) months post-treatment was compared to reference data from the Maastricht Aging study. The Gondi model was applied to the dosimetric data and model predictions were compared to actual neurocognitive outcome. Results: A total of 29 patients met inclusion criteria. Mean dose in EQD2 Gy to the bilateral hippocampus was 39.8 Gy (95%CI 34.3–44.4 Gy), the median dose to 40% of the bilateral hippocampus was 47.2 EQD2 Gy. The model predicted a risk of memory impairment exceeding 99% in 22 patients. However, only seven patients were found to have a significant decline in AVLT-dr score. Conclusions: In this dataset of only LGG patients treated with radiotherapy the hippocampus NTCP model did not perform as expected to predict cognitive decline based on dose to 40% of the bilateral hippocampus. Caution should be taken when extrapolating this model outside of the range of dose-volume parameters in which it was developed.